Power, difference and mobility: feminist advances in migration studies - Silvey, Rachel (Progress in human geography, 2004)
The feminist migration literature in geography has contributed to bringing several critical social theoretical themes to the forefront of migration studies. Specifically, feminists have foregrounded the politics of scale, mobility as political process, questions of subjectivity/identity and critical theorizations of space and place. This article provides an overview of the feminist migration literature organized around these themes. In addition, it argues that feminist migration studies can play a pivotal role in the ongoing project of marrying the materialist concerns of political economy to those of critical social theorists.